Teachers' strategies in teaching english for inclusive students: a case study in Balirejo public elementary school - Handung Jaya, Patria; Berliana Putri, Ade (Universitas Ahmad Dahlan, 2025)
Teaching children is not only about the material but how we deliver the material to them to achieve the goal of learning. The challenges are real especially when we teach children with special education need (SEN) in an inclusive classroom, where they are together with regular children. In addition, subject that has to be taught is English language, which used to be removed from an elementary school’s curriculum. This research aims to find out teachers’ strategies in teaching English for inclusive students as well as the challenges they face. This is a case study in Balirejo Public Elementary School, Yogyakarta which is conducted qualitatively by interviewing the English teachers and the Headmaster there. The result shows that pleasurable activities and good communication can effectively increase students’ motivation which become the biggest challenge. Students’ character, ability, and mood are also other challenges found by the teachers since the students in inclusive classrooms are varied. The researchers hope that this research can create more awareness to teachers, schools, and government related to English teaching and learning process in inclusive classrooms.